Probing IMF using nanodust measurements from inside Saturn's magnetosphere. Issue 12 (18th June 2013) - Hsu, H.‐W.; Hansen, K. C.; Horányi, M.; Kempf, S.; Mocker, A.; Moragas‐Klostermeyer, G.; Postberg, F.; Srama, R.; Zieger, B.
Abstract: [1] We present a new concept of monitoring the interplanetary magnetic field (IMF) by using in situ measurements of nanodust stream particles in Saturn's magnetosphere. We show that the nanodust detection pattern obtained inside the magnetosphere resembles those observed in interplanetary space and is associated with the solar wind compression regions. Our dust dynamics model reproduces the observed nanodust dynamical properties as well as the detection pattern, suggesting that the ejected stream particles can reenter Saturn's magnetosphere at certain occasions due to the dynamical influence from the time‐varying IMF. This method provides information on the IMF direction and a rough estimation on the solar wind compression arrival time at Saturn. Such information can be useful for studies related to the solar wind‐magnetosphere interactions, especially when the solar wind parameters are not directly available. Key Points: A new method to probe IMF with nanodust measurements inside the magnetosphere Under changing IMF, ejected nanoparticles can re‐enter Saturn‐s magnetosphere IMF direction and solar wind compression arrival time can be derived